Oral Administration of Flavonifractor plautii Strongly Suppresses Th2 Immune Responses in Mice - Ogita, Tasuku; Yamamoto, Yoshinari; Mikami, Ayane; Shigemori, Suguru; Sato, Takashi; Shimosato, Takeshi (Frontiers in Immunology, 2020)
The bacterium Flavonifractor plautii (FP), which is found in human feces, has been reported to participate in catechin metabolism in the gut, but its effects on immune function are unclear. We assessed the effect of oral administration of FP on the immune response in ovalbumin (OVA) -sensitized mice. We demonstrated that the FP treatment suppressed accumulation of the interleukin (IL) -4-encoding mRNA in splenocytes from OVA-sensitized mice. Moreover, oral administration of FP down-regulated OVA-specific immunoglobulin E production in serum. In animals of the FP + OVA group, the proportion of FP was increased in the mesenteric lymph nodes (MLNs), as was the proportion of Deferribacteres in the cecum. Oral administration of FP may inhibit the Th2 immune response by incorporation into the MLNs and/or by inducing changes in the gut microbiota. Thus, FP may be useful in alleviating antigen-induced Th2 immune responses.